Acute Cardiovascular Care Association position statement for the diagnosis and treatment of patients with acute myocardial infarction complicated by cardiogenic shock: A document of the Acute Cardiovascular Care Association of the European Society of Cardiology. Issue 2 (1st March 2020) - Zeymer, Uwe; Bueno, Hector; Granger, Christopher B; Hochman, Judith; Huber, Kurt; Lettino, Maddalena; Price, Susanna; Schiele, Francois; Tubaro, Marco; Vranckx, Pascal; Zahger, Doron; Thiele, Holger
Abstract: Most of the guideline-recommended treatment strategies for patients with acute coronary syndromes have been tested in large randomised clinical trials. Still, a major challenge is represented by patients with acute myocardial infarction admitted with impending or established cardiogenic shock. Despite early revascularization the mortality of cardiogenic shock remains high and roughly half of patients do not survive until hospital discharge or 30-day follow-up. However, there is only limited evidence-based scientific knowledge in the cardiogenic shock setting. Therefore, recommendations and actual treatments are often based on retrospective or prospective registry data and extrapolations from randomised clinical trials in acute myocardial infarction patients without cardiogenic shock. This position statement will summarise the current consensus of the diagnosis and treatment of patients with acute myocardial infarction complicated by cardiogenic shock based on current evidence and will provide advice for clinical practice.